Optimum Design Of URRG-AUV Propeller Using PVL - Muhamad Husaini, Muhamad Husaini; Samad, Zahurin; Arshad, Mohd Rizal (Universiti Sains Malaysia, 2008)
Common practice in AUV propulsion system is utilizing the propeller and motor to generate the thrust. The performance underwater vehicle is directly influence by propulsion system efficiency.